2012
DOI: 10.1159/000338946
|View full text |Cite
|
Sign up to set email alerts
|

Increased Level of Antibodies Cross-Reacting with Ves v 5 and CRISP-2 in MAR-Positive Patients

Abstract: Background: Anti-sperm antibodies (ASA) have been described to be involved in immunological infertility. A possible antigen for ASA is the human cysteine-rich secretory protein 2 (CRISP-2), a sperm surface protein important in sperm-oocyte interaction. Furthermore, anti-CRISP-2 antibodies were shown to decrease fertility rates in vitro. Recently, we have reported cross-reacting antibodies recognizing CRISP-2 and antigen 5 from yellow jacket venom (Ves v 5) in human serum. Methods: Here, we investigated anti-Ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
4
1
1
Order By: Relevance
“…These autoantibodies lead to sperm immobilization and bind along the sperm surface, including the head, where CRISP-2 is localized (Brunner-Agten et al 2013). Additionally, the fact that these autoantibodies can bind to Ves V 5 led the authors to hypothesize that ASA-positive men may have a higher risk to develop wasp allergy (Brunner-Agten et al 2013). However, ASA positivity in this study was considered above 10% which is very different from the WHO reference value.…”
Section: Autoimmune Diseasescontrasting
confidence: 54%
See 1 more Smart Citation
“…These autoantibodies lead to sperm immobilization and bind along the sperm surface, including the head, where CRISP-2 is localized (Brunner-Agten et al 2013). Additionally, the fact that these autoantibodies can bind to Ves V 5 led the authors to hypothesize that ASA-positive men may have a higher risk to develop wasp allergy (Brunner-Agten et al 2013). However, ASA positivity in this study was considered above 10% which is very different from the WHO reference value.…”
Section: Autoimmune Diseasescontrasting
confidence: 54%
“…The authors demonstrated that ASA-positive men had a higher incidence of allergy against Hymenoptera venom, and the results also showed a high amount of autoantibodies that cross-react with both CRISP-2 and Ves V 5 allergen. These autoantibodies lead to sperm immobilization and bind along the sperm surface, including the head, where CRISP-2 is localized (Brunner-Agten et al 2013). Additionally, the fact that these autoantibodies can bind to Ves V 5 led the authors to hypothesize that ASA-positive men may have a higher risk to develop wasp allergy (Brunner-Agten et al 2013).…”
Section: Autoimmune Diseasesmentioning
confidence: 99%
“…On the other hand, Fu et al 22 recently developed an enzyme‐linked immunosorbent assay (ELISA) using anti‐actin‐like protein (ACTL)7a antibodies because they thought that previously available tests of ASA detection showed only the binding of antibodies on the sperm surface, but no antigenic information could be applied 23‐25 . They have focused on the sperm‐specific expression protein ACTL7a and found that ACTL7a could be recognized by the antibodies contained in infertile serum, which could reduce mouse fertility rates to zero 26 .…”
Section: Detection Of Anti‐sperm Antibodiesmentioning
confidence: 99%
“…Several tests are available to detect ASA in either semen or serum, including ‘direct’ tests for antibodies bound to the sperm and ‘indirect’ tests in sperm-free fluids such as serum. Previously available tests of ASA detection showed only the binding of antibodies on the sperm surface, but no antigenic information could be applied 10 11 12 . Antibodies derived from accurate, specific spermatozoa antigens should be detected and assessed for possible use in clinical diagnosis.…”
mentioning
confidence: 99%